Multivariate genome-wide analysis of sarcopenia reveals genetic comorbidity with urological diseases - Feixiang Yang; Xiangyu Zhang; Wei Dai; Ke Xu; Yunyun Mei; Tianrui Liu; Kun Wang; Qianjun Liang; Peng Guo; Chaozhao Liang; Jialin Meng (Experimental Gerontology)
Introduction: Sarcopenia is a prevalent age-related disorder characterized by progressive loss of muscle mass, strength, and physical performance. While genome-wide association studies (GWAS) have explored isolated traits, the multifactorial genetic architecture underlying sarcopenia remains poorly defined. In this study, we constructed a comprehensive genetic factor to explain the genetic architecture of sarcopenia, and explore causal associations, genetic comorbidities, and mediating pathways linking sarcopenia to 30 urological diseases. Methods: Based on the European Working Group on Sarcopenia in Older People (EWGSOP) criteria, six sarcopenia-related phenotypes were selected. A multivariate GWAS framework using genomic structural equation modeling (genomic SEM) was constructed, with an effective sample size of 651,820 individuals. Bidirectional Mendelian randomization (MR) was employed to assess causal relationships between sarcopenia and 30 urological diseases. Genetic correlation, tissue-specific heritability enrichment, shared risk genes, and gene set enrichment analyses were conducted to dissect genetic comorbidities between sarcopenia and urological diseases. Multi-omic mediation analysis was conducted to identify potential pathways mediated by blood proteins, metabolites, and immune traits. Results: Multivariate GWAS identified 215 loci and 30,869 single-nucleotide polymorphisms (SNPs) associated with polygenic architecture of sarcopenia. Bidirectional Mendelian randomization revealed causal links between sarcopenia and urological diseases, notably hyperplasia of prostate (BPH; OR = 1.17, P = 0.043) and acute tubulointerstitial nephritis (ATIN; OR = 1.14, P = 0.028). Genetic comorbidity analyses identified local genetic correlations between sarcopenia and BPH, and highlighted tissue-specific heritability enrichment in Cells Cultured fibroblasts tissue for both traits, while no genetic correlation was found with ATIN. We identified 75 shared risk genes for sarcopenia and BPH, which were enriched in cellular component biogenesis, RNA binding, and metabolic pathways. Multi-omic mediation analyses prioritized 17 metabolites and proteins linking sarcopenia to BPH and ATIN, though no significant immune mediators were identified. Conclusion: These findings unveil a shared genetic architecture between sarcopenia and urological diseases, especially BPH, with heritability enrichment in fibroblast tissue and metabolic dysfunction emerging as the significant overlapping pathway.